Method of determining dynamic retention of mesh phase separator - Давыдов, Сергей Александрович (Eastern-European Journal of Enterprise Technologies, 2010)
In given work the engineering design procedure of dynamic retention of mesh phase’s delimiters is presented. This allows to determine functionability of means fuel continuity support in dynamic conditions at a stage of outline designing.